Unveiling the electrochemical reactivity of urethane toward different bond formations and application to polyurethane deconstruction via C―N bond formation - Singh, Adarsh; Samanta, Ramesh C. (Angewandte Chemie-International Edition, 2026)
Plastics are essential, and their production is increasing. The rate of plastic recycling is extremely low, and end-of-life plastics are sent to landfills and oceans, which is alarming. Mechanical recycling is not a viable solution because it produces downgraded materials. Efficient methods for chemical recycling of plastics are essential. Polyurethane is a widely used plastic, and the presence of very stable carbamate functionality makes its recycling extremely difficult. Existing methods require expensive reagents and harsh reaction conditions, such as high temperature, high pressure, and precious metal catalysts such as iridium and ruthenium. Electrochemistry can potentially be used to develop sustainable methods that can operate under milder conditions using fewer reagents. We disclose that urethane serves as an efficient carbamoylation reagent under electrochemical conditions at lower temperatures to form C & horbar;N, C & horbar;P, and C & horbar;C bonds. This method works successfully to deconstruct commercially available polyurethane using different amines. Furthermore, the robustness of the method has been tested on daily life plastics made of polyurethane with additives, such as flexible tubing and mobile covers. This method has also been applied for polymer backbone editing by converting the urethane linkage to urea upon reaction with diamine.
Keywords: carbamoylation; electroreduction of carbamate; polymer upcycling; polyurethane deconstruction; sustainabiliy